Life cycle Theory Test in the Dividend Policies of Companies in Tehran Stock Exchange - Hossein Etemadi; Ali Asghar Anvari rostami; Vahid Ahmadian (مطالعات تجربی حسابداری مالی, 2013)
Abstract: The main objective of this study is to investigate the effect of the life cycle of the company's on dividend policy of the company which is accepted on the Tehran Stock Exchange. In this study, the ratio of dividends to the earnings per share and dividends to the company size are considered as the dependent variables and life cycle of the company is considered as independent variable. At first a statistical sample is separated by using variables, sales growth, age, and capital expenditure of the company's growth, maturity and decline then hypotheses of the study have been tested by using ANOVA and LSD tests. Analyses of 435 years - the company during the years 1386 to 1390 show that the company's dividend policy at different stages of the life cycle (growth, maturity and decline) differ. The results indicate that the average ratio of dividends to market value of equity of the sample firm's growth, maturity and decline vary. Accordingly, it is recommended to financial analysts to concern life cycle as a key factor when evaluating the current and future performance and financial structure of the company. for doing accurate analysis of financial condition and anticipated interest payments decisions, it is better to determine the company's life cycle.